TNFAIP3 DRIVES COLITIS THROUGH DEATH CELL AND TNFα PRODUCTION. (22nd January 2022) - Huerta, Alvaro Torres; Ruley-Haase, Katelyn; Boger-May, Antonia; Boone, David
Abstract: IBD is characterized by inflammation involving a complex interplay between innate and adaptive immunity, non-immune cells, and intestinal microbes. To understand the contributions of innate immunity to inflammation during colitis we have developed a chronic model of innate immune-mediated colitis wherein RAG1 -/- mice are crossed with mice expressing TNFAIP3 in intestinal epithelial cells (villin-TNFAIP3 mice). These villin-TNFAIP3 x RAG1 -/- (TRAG) mice develop early onset, 100% penetrant, chronic colitis driven by gut microbes. To understand the inflammatory signals that lead to innate colitis in this model, we crossed TRAG mice with TNFα -/- mice (FRAG mice) and compared the severity of colitis in TRAG vs. FRAG mice. In addition, we characterized TNFα-producing myeloid populations from the lamina propria of TRAG mice. Finally, we assessed the expression and localization of proteins involved in cell death pathways, to unravel the mechanisms driving innate-immune mediated colitis. Our results show that, compared to RAG1 -/- mice, TRAG mice have significantly increased numbers of lamina propria leukocytes, including increased numbers of neutrophils, inflammatory monocytes, macrophages, dendritic cells, and innate lymphoid cells. TRAG mice lacking TNFα (FRAG mice) had significantly lower numbers of all these leukocyte subsets. Consistent with this, FRAG mice had significantly lower histological colitis scores, compared to TRAG mice. Inflammatory monocytes, monocytes, macrophages, and neutrophils were found to be the main sources of TNFα production, while TNFα production was null or minimal in dendritic cells, natural killer cells, ILC1, ILC3 and IC2. Macrophages and inflammatory monocytes in TRAG mice were characterized by the expression of iNOS, whereas macrophages and monocytes of FRAG and RAG1 -/- mice were notably marked by Arginase1 expression. Localization of active caspase3, phosphor-MLKL and TUNEL positive cells indicated extensive epithelial crypt cell death in TRAG mice that was markedly suppressed in FRAG mice. Together our results show that TNFα drives innate immune mediated colitis, potentially through induction of IEC necroptosis. TNFAIP3 is well known as a negative regulator of receptor-mediated NFκB and MAPK activation and therefore attempts to increase TNFAIP3 expression are considered promising avenues for prevention of inflammation. The present study, indicating that intestinal epithelial cell expression of TNFAIP3 drives TNFα-induced IEC death and innate colitis, highlights potential tissue-specific roles for TNFAIP3 that should be considered in the paradigm of TNFAIP3 as a target for prevention of inflammation.